Application of Fourier Transform Infrared Spectroscopy for Analysis, Authentication and Monitoring of Oxidative Stability of Edible Oils - Rohman, Abdul (2010)
Fourier transform infrared (FTIR) has become powerful analytical technique in the study of fats and oils. The objective of this study was to use FTIR spectroscopy combined with certain chemometrics techniques to analyze, authenticate, and to monitor the oxidative stability of selected edible fats and oils. FTIR spectra combined with principal component analysis (PCA) and cluster analysis using absorbances as variables at 16 frequencies have been successfully used for differentiation of lard (LD). Among sixteen edible fats and oils, extra virgin olive oil, rice bran oil, and chicken fat were close to LD compared with others. The presence of LD in binary mixtures with beef (BF), chicken, (CF), and mutton fat (MF) was analyzed using FTIR spectroscopy combined with partial least square (PLS) at fingerprint region of 1,500 – 900 cm-1. The coefficients of determination (R2) for the relationship between actual value of LD (x-axis) and FTIR predicted values (y-axis) in BF, CF, and MF were 0.999 0.998, and 0.995, respectively. Frequencies of 1,500 – 1000 cm-1 were selected for quantification of LD in the binary mixtures with selected vegetable oils of canola, corn, extra virgin olive, soybean, and sunflower oils. These frequency regions are also preferred for analysis of LD in quaternary systems using first derivative spectra with R2 and root mean square error of calibration (RMSEC) values of 0.997 and 0.773 % (v/v), respectively. Furthermore, in food systems using meat ball formulation, LD has been successfully determined at 1,200 – 1,000 cm-1 with R2 and RMSEC values of 0.999 and 0.442 % (v/v), respectively. FTIR spectroscopy in combination with PLS and principle component regression (PCR) was also used for quantifying VCO. VCO in binary mixtures with palm oil (PO) is better determined using PLS at combined frequencies of 1,120 – 1105 and 965 – 960 cm-1 with R2 and RMSEC values obtained were 0.999 and 0.758 % (v/v), respectively. These frequencies were also well suited for quantitative analysis of VCO in binary mixtures with olive oil (OO). Furthermore, frequencies at 1,200 - 1,000 cm-1 using PLS and second derivative spectra was applicable for quantitative analysis of VCO in ternary mixtures with PO and OO. Authentication analysis of cod liver oil (CLO) from LD was performed using FTIR spectroscopy at frequency 1,035 – 1030 cm-1. In addition, BF, CF, and MF were also successfully determined using PLS at certain optimized frequencies. Discriminant analysis (DA) can successfully classify CLO and CLO adulterated with animal fats at certain frequency regions. FTIR spectroscopy was also used for authentication analysis of extra virgin olive oil (EVOO) and virgin coconut oil (VCO). FTIR normal spectra along with PLS was preferred over PCR for quantification of studied vegetable oils in EVOO and VCO, except for palm oil which was better determined with first derivative spectra. The R2 values obtained were higher than 0.99 in calibration model. DA successfully classified EVOO and VCO and those adulterated with some vegetable oils. Analysis of fatty acid changes of the authentic oils (CLO, EVOO, and VCO) due to the adulteration practice can complement the FTIR spectral measurements. FTIR spectroscopy was used to evaluate the oxidative stability of vegetable oils with high mono- and polyunsaturated fatty acids, namely corn, rice bran, soybean, and sunflower oils. The oils were subjected to thermal oxidation at 160 oC for 120 h. Each 12 h interval, the oils were analyzed for its specific absorptivity of conjugated dienes (CDs) and trienes (CTs), p-anisidin values (p-AV) and FTIR spectra changes at frequencies of 3470, 3008, 1743, 1655, 967, and 721 cm-1. FTIR spectral changes at 3008 cm-1 can be used to predict the level of oxidation, especially for determination of CDs, CTs, and p-AV values. In conclusion, this study showed that FTIR spectroscopy combined with suitable chemometrics technique can provide reliable analytical tool to analyze and to authenticate edible fats and oils. FTIR spectroscopy could also potentially be used for routine monitoring the oxidative stability of fats and oils.